2012
DOI: 10.5664/jcsm.1908
|View full text |Cite
|
Sign up to set email alerts
|

Overdrive Ventricular Pacing in Pacemaker Recipients with Permanent Atrial Fibrillation and Sleep Apnea

Abstract: Study Objectives: Cardiac pacing is ineffective in obstructive sleep apnea (SA), but it can alleviate central SA/CheyneStokes respiration (CSA) in patients with heart failure (HF). We examined whether overnight overdrive ventricular pacing (OVP) has an effect on SA in pacemaker recipients with permanent atrial fi brillation (AF). Methods: An apnea-hypopnea index (AHI) ≥ 15 was confi rmed in 28/38 patients screened by fi nger pulse oximetry during overnight ventricular pacing at a backup rate of 40 bpm (BUV40).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…One study has reported a high proportion of CSA (79%) in a group of pacemaker recipients with permanent AF [86]; this was probably a result of a high rate of heart failure and depressed left ventricular ejection function in this study population. Another study in AF patients with normal left ventricular function showed prevalence rates of 31% for CSA and 43% for OSA [87]. Future studies are needed to clarify mechanisms responsible for AF in CSA and whether adaptive servo ventilation is helpful to prevent AF and to improve symptoms and decrease mortality in heart failure AF-patients.…”
Section: Central Sleep Apneamentioning
confidence: 92%
“…One study has reported a high proportion of CSA (79%) in a group of pacemaker recipients with permanent AF [86]; this was probably a result of a high rate of heart failure and depressed left ventricular ejection function in this study population. Another study in AF patients with normal left ventricular function showed prevalence rates of 31% for CSA and 43% for OSA [87]. Future studies are needed to clarify mechanisms responsible for AF in CSA and whether adaptive servo ventilation is helpful to prevent AF and to improve symptoms and decrease mortality in heart failure AF-patients.…”
Section: Central Sleep Apneamentioning
confidence: 92%
“…Although initial proof of concept work appeared to demonstrate improvement in central and obstructive apnea with an overdrive pacing intervention 86 , subsequent studies have failed to show consistent findings 46 . Recent data, however, suggest that in those with moderate to severe SDB, overdrive pacing at a rate 20 bpm above the mean nocturnal heart rate resulted in a statistically significant reduction in central apnea burden, however, it is unclear whether this burden reduction translates into clinical significance (central apnea hypopnea index of 23.9 ± 11.8 versus 19.1 ± 12.7) 87 . Unlike the disappointing results of overdrive pacing, cardiac resynchronization therapy (biventricular pacing) appears to be an effective strategy in improving SDB in HF likely because it improves left ventricular EF, increases cardiac output, reduces pulmonary venous pressure and therefore reduces the tendency towards hyperventilation and hypocapnia.…”
Section: Impact Of Sleep Disordered Breathing Treatment On Arrhythmiamentioning
confidence: 99%
“…A recent randomised cross-over trial showed in 28 patients with a mean age of 77.9 years that an overpacing of 20 beats per min over the sensored mean heart rate resulted in a significant reduction of central events [87] (table 5). The only age-stratified study compared CRT and atrial overpacing (AOP) in 15 subjects (mean age 74 years), and found that AOP resulted in a higher reduction of all apnoea events, but not hypopneas, compared to a lower fixed heart rate (mean apnoea index 18 with AOP versus 24 with fixed lower rate coming from a mean baseline of 35 events per h).…”
Section: Atrial Overpacingmentioning
confidence: 99%